Feasibility and acceptability of take‐home naloxone for people released from prison in New South Wales, Australia. (17th August 2020) - Moradmand‐Badie, Banafsheh; Tran, Lucy; Oikarainen, Noora; Degenhardt, Louisa; Nielsen, Suzanne; Roberts, Jillian; Ward, Stephen; Bowman, Julia; Larney, Sarah
Abstract: Introduction and Aims: To assess the feasibility and acceptability of a take‐home naloxone program for people with a history of opioid use released from prison in New South Wales, Australia. Design and Methods: Cross‐sectional interviews with people with a history of opioid use who were recently released from prison ( n = 105), and semi‐structured interviews with key clinical and operational staff of Justice Health and Forensic Mental Health Network and Corrective Services NSW ( n = 9). Results: Among people with a history of opioid use who had recently left prison, there was very high awareness of the elevated risk of overdose following release from prison (95%) and the potential for naloxone to reverse an opioid overdose (97%). Participants considered that their personal risk of overdose was low, despite ongoing opioid use being common. Participants were largely supportive of take‐home naloxone, but the majority (83%) stated that proactively obtaining naloxone would be a low priority for them following release. Key informants were supportive of introducing naloxone training and supply and identified barriers to implementation, including adequate resourcing, identifying the population for training, and developing an appropriate model of training and implementation. Discussion and Conclusion: There was widespread support for naloxone training in custody and distribution at release among people recently released from prison and key stakeholders in health‐care provision and prisons administration. As proactively accessing naloxone is a low priority for patients, naloxone supply at release may be more effective than programs that refer releasees to local pharmacies, but developing a sustainable supply model requires consideration of several barriers.